Sebuah Pertahanan Terpadu: Menggabungkan Aspek Media Sosial, Siber dan Teknologi dalam Konteks Perang Asimetris - Iwan Setiawan; Fauzia G. Cempaka; Yono Reksoprodjo (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
Integrated defense is a core component of Indonesia's defense and security strategy, designed to protect the country's sovereignty, territorial integrity, and national safety from both physical and non-physical threats, especially cyber threats. With the rapid technological advancements and the rise of social media, cyber threats have become a significant concern as they impact various aspects of national security. Indonesia's large population of internet and social media users heightens the urgency for strategic attention to cyber defense. The government has introduced various policies and regulations, such as those by the Ministry of Defense, to strengthen cyber security and integrate it into national defense mechanisms. This study uses a qualitative descriptive approach, analyzing literature and legal frameworks to highlight the significance of integrated defense in addressing modern, asymmetric threats. In asymmetric warfare, non-military means, including cyber-attacks, are used to weaken a nation's ideological, political, economic, and social systems. The research emphasizes the need for a comprehensive and adaptive strategy, involving collaboration between the government, private sector, and civil society, to counter these complex threats. Strengthening cyber defense through education, training, and public awareness is crucial for safeguarding Indonesia's national security in the digital age.